(untitled) (Annals of Medical Research, 2021)
Aim: We reviewed the files of 188 patients diagnosed with acute lymphoblastic leukemia at Pediatric Hematology Department, Necmettin Erbakan University Faculty of Medicine, Konya, between April 2006 and April 2016 retrospectively. 167 patients, who had sufficient records and accepting to participate in the study, were included. Patients were classified 3 groups according to their treatment protocols. These protocols were Saint Jude Total Therapy (St. Jude) protocol, Berlin-Frankfurt-Munster 2000 (BFM 2000) protocol and BFM 2009 protocol. Acute lymphoblastic leukemia (ALL) is a malignant disorder characterized with clonal enlargement of lymphoid progenitor cells. It is most common malignancy in childhood. Recent developments in immunologic and genetic methods have significantly altered the diagnostic and classification approaches. Nowadays advanced studies such as immunologic and cytogenetic studies have become more important in prognosis and treatment response. In this study, we aimed to present the clinical and laboratory features of patient with ALL who were followed in our Pediatric Hematology Clinic (Necmettin Erbakan University Faculty of Medicine, Konya) and determine the factors affecting the mortality and morbidity in patients with ALL.Results: When the results of the study were evaluated, we found that uric acid levels, blast ratio on the 15th day bone marrow evaluation, presence of relapse and relapse type were effective on overall survival. Also, we found that blast ratio on 15th day bone marrow evaluation, high levels of uric acid, and lactate dehydrogenase (LDH) were effective for event-free survival. Conclusion: In conclusion, our overall survival and disease-free survival rates are similar to those performed by St. Jude Total therapy XIIIB, BFM 2000 and BFM 2009 protocol.